Confucian Ethical Healing and Psychology of Self-cultivation - Hwang, Kwang-Kuo (Research in the social scientific study of religion, 2017)
In view of the inappropriateness of blind transplanting Western positive psychology into East Asian societies, this article proposes a model of Confucian ethical healing for developing the psychology of self-cultivation. Hwang’s (2011, 2015) Mandala model of self is modified with a serious consideration of the Self as suggested by Jung’s psychology. Because Confucian ethics and morality are supposed to be the transcendental formal structure for sustaining the life-worlds of Chinese people (Hwang, 2016), it can be used as a basis for developing Confucian ethical healing in East Asian societies. All practices of self-cultivation from the cultural heritage of Taoism, Buddhism, particularly Confucianism, may help an individual to attain the goal of maintaining psychosocial homeostasis which can be conceptualized as an indicator for peaceable psychology in East Asia (Dueck & Reimer, 2009)